Saintly animals. A semiotic perspective on changing models of sanctity and personhood - Jenny Ponzo (Ocula)
This paper exposes the results of a research that focuses on the changing thresholds of the notions of sanctity and personhood in Catholic culture, with an emphasis on the contemporary age. In particular, it explores the relationship between saints and animals, thus identifying three main categories, involving an increasing degree of agency attributed to the animals. The first kind of relationship consists in the association of an animal to a saintly character: in this kind of relationship, the animal mainly works as a figure of the saint. The second is the representation of animals with a narrative role in the life story of the saint: in this case, animals play an active role in the story, often as Helpers. The third concerns the representation of animals themselves as saints. This third case is particularly interesting, because animals are not limited to ancillary roles in relation to a human protagonist, but become themselves the protagonists and embody exemplary models, proposed to the imitation of human beings in reason of their moral superiority. These narratives are representative of the fact that in our age the thresholds of the concept of sanctity are shifting under various and relevant aspects. The representations of animals as saints, the growingly shared conviction about their right to be considered as persons, the fact that some individual animals are considered exemplary characters embodying a particular idea of sanctity, are all clear examples of a worldview admitting that moral models and personhood can be found even outside the borders of the human form of life.